(untitled) (Eureka Journal of Business, Economics & Innovation Studies, 2026)
This article examines the organizational and methodological aspects of preparing students for teaching, specifically, preparing them to design learning situations important for independent teaching. The article also identifies the types, forms, and methods of learning situations, as well as the principles for creating successful situations.